Factors influencing length of hospital stay in an acute psychogeriatric unit. Issue 4 (5th April 2021) - Koskas, Pierre; Bourdonnec, Lauriane; Kohler, Samuel; Romdhani, Mouna; Drunat, Olivier
Abstract: Background: Dementia patients represent a significant volume of hospital admissions and impose a high cost on the health system. There is a significantly higher length of hospital stay (LOHS) for elderly demented patients. Methods: This study was carried out in an acute psychogeriatric unit specialising in behavioural and psychological symptoms in dementia. Socio‐demographic, cognitive and nutritional variables were taken into account. We first compared the patients returning home (group 1) after hospital discharge with those transferred to the rehabilitation psychogeriatric unit (group 2). We secondarily explored the correlation of LOHS with the variables described above for the two groups. Results: We retained 92 patients (of 375 admitted) for our study, mean age 83.9 ± 6.6, Mini‐Mental State Examination 12.8 ± 9.6, initial weight 61.7 ± 13.2 kg and body mass index 24.8 ± 4.7. We noticed significant differences in cognitive status but not in nutritional variables or in socio‐demographic characteristics between the two groups. Only weight in nutritional variables was significantly associated with LOHS in the acute psychogeriatric unit. Conclusions: Our main finding underlined the key role of cognitive factors in patient discharge home. And only initial weigh seems have an influence in LOHS instead of cognitive status or socio‐demographic characteristics.